Targeting of EU Development Assistance in Asia - Smolaga, Mateusz (New Dynamics in Asia, 2020)
Official Development Assistance (ODA) exists as a response to the needs of the World’s weaker developing nations. Intuitively, we might expect that greater ODA should be provided to those in greatest need, while more developed countries should receive less. When we look at the actual data on the European Union’s (EU) targeting across Asia, the focus of this paper, we see that this pattern is usually met. In cases where this pattern is not met we need to understand why. To assess the effectiveness of EU ODA targeting between 2001 and 2017 four separate indicators were used. Using these, we tested how well the actual Official Development Assistance/Human Development Indicator (HDI) relationships map onto the predetermined ideal of high ODA to low HDI score, and vice versa. These tests were also applied to ODA data of the other major donors active across Asia. The EU’s targeting in matching a high ODA to low HDI pattern is generally effective, but the data shows a number of interesting anomalies. A closer inspection of the data suggests that these are the result of the EU placing its own political and/or economic interests above those of countries in receipt of its ODA. The analysis shows that the EU has improved its ODA targeting across Asia. However, this improvement only managed to achieve a level of moderate correlation towards the ideal in 2017 from its unimpressively low correlation recorded in 2001.